Regional Convergence in Latin America - Sutton, Bennett (IMF Working Papers; Working Paper, 2006)
This paper presents empirical evidence on convergence of per capita output for regions within six large middle-income Latin American countries: Argentina, Brazil, Chile, Colombia, Mexico, and Peru. It explores the role played by several exogenous sectoral shocks and differences in steady states within each country. It finds that poor and rich regions within each country converged at very low rates over the past three decades. It also finds evidence of regional "convergence clubs" within Brazil and Peru- the estimated speeds of convergence for these countries more than double after controlling for different subnational levels of steady state. For the latter countries and Chile, convergence is also higher after controlling for sector-specific shocks. Finally, results show that national disparities in per capita output increased temporarily after each country pursued trade liberalization.